The Business Of Property: What Determines Profit? - Mubarok, Faizul; Nurmailia, Avhita; Nabila, Bela; Azzahrah, Fatimah (Balance Vocation Accounting Journal, 2025)
The aim of this study is to investigate the impact of inflation, interest rates, company age, leverage and liquidity as variables to profitability of company in the property sector. As this study used the purposive sampling method, the sample consists of 10 companies and resulted in 320 observations within 2015 to 2022 which are the quarterly financial report. The findings show that variables of inflation, liquidity and leverage are significantly influence to the profitability of property companies. While, the company age and interest rates are only have slight effect to the profitability. These findings will provide essential information where it useful for the practitioners and stakeholders in property industry so they can comprehend the role of variables impact to the financial aspect of the companies. Thus, property companies can mitigate the detrimental effect risking causes on their financial performance and make a strategic decision to achieve high profitability despite the frequent changes in the market.